Group Cognitive Behavioral Therapy for Substance Use Disorders Among Psychiatric Inpatients in a Medically Underserved Area: An Intervention for Opioid Misuse. (May 2023) - Buckner, Julia D.; Scherzer, Caroline R.; Crapanzano, Kathleen A.; Morris, Paige E.
Objectives: Opioid misuse is a serious public health concern, yet few people seek treatment for this condition. Hospitals may be one opportunity to identify those with opioid misuse and to teach them skills to help manage their opioid misuse upon discharge. We tested the relationship between opioid misuse status and motivation to change substance use among patients admitted with substance misuse to an inpatient psychiatric unit in a medically underserved area in Baton Rouge, Louisiana, who attended at least 1 group session of motivation enhancement therapy combined with cognitive behavioral therapy (MET-CBT) from January 29, 2020, through March 10, 2022. Methods: Of the 419 patients in our sample, 86 (20.5%) appeared to misuse opioids (62.5% male; mean age, 35.0 y; 57.7% non-Hispanic/Latin White). At the beginning of each session, patients completed 2 measures of motivation—importance and confidence to change substance use—from 0 (not at all) to 10 (most). At the end of each session, patients rated perceived session helpfulness from 1 (extremely hindering) to 9 (extremely helpful). Results: Opioid misuse was associated with greater importance (Cohen d  = 0.12) and confidence (Cohen d  = 0.13) to change substance use and with attending more MET-CBT sessions (Cohen d  = 0.13). Patients with opioid misuse rated sessions as highly helpful (score of 8.3 of 9), and these ratings did not differ from patients who used other substances. Conclusions: Inpatient psychiatry hospitalizations may provide an opportunity to identify patients with opioid misuse and introduce these patients to MET-CBT to learn skills to manage opioid misuse upon discharge.